Review of Three Essays in Comparative Literature: Matter and Method by A. Owen Aldridge - Asst. Lect. Najlaa Muqdad Said (مجلة العصر للعلوم الانسانية والاجتماع, 2026)
The review examines three essays from Comparative Literature: Matter and Method by A. Owen Aldridge. Harry Levin’s “France-Amérique: The Transatlantic Refraction” examines the intellectual and cultural dialogism between America and France. The author discusses the interpretation of American history, literature, and identity through French perspectives and how such interpretations create a kind of “refraction” or transformation of the original meanings. Martin Jarret-Kerr’s “The Conditions of Tragedy” explores the dehumanization tendencies and anti-novel in modern French literature, especially in Robbe-Grillet’s work. The essay investigates the relation between tragedy and personality in addition to Christian thought. Walter J. Ong’s “Evolution, Myth, and Poetic Vision” explores the role of Darwinism and modern scientific thought in shaping the imagination of modern man and influencing poetry. This reflection has its consequences on poetry in terms of cyclical patterns in modern poetry. Those three essays show different approaches to comparative literature, addressing transatlanticism and cultural change.